HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN EMOSIONAL PADA ANAK SEKOLAH DI SDN NOGOTIRTO - Bintang, Sri; Dwi Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The emotional development of school-age children is influenced by various factors, one of which is parenting patterns. This study aims to determine the relationship between parenting patterns and children's emotional development at SDN Nogotirto Yogyakarta in 2026. The study used a quantitative correlational design with a random sampling technique. The sample consisted of 53 students from a population of 114 students. Data were collected using the PSDQ and SDQ, then analyzed using the Spearman Rank test. The results showed a significant relationship between parenting patterns and children's emotional development (p = 0.000; r = 0.567). These results indicate a meaningful relationship between parenting patterns and children's emotional development. This study is expected to be a consideration for parents and schools in supporting children's emotional development through the implementation of appropriate parenting patterns.